MODELING AN EXPERT SYSTEM TO IMPROVE PRODUCTS AND PROCESSES IN THE MILK PRODUCTION USING THE UML - Neto, Mario Mollo; Nääs, Irenilza de Alencar (Revista Brasileira de Engenharia de Biossistemas, 2010)
The animal precision production allows the development of automated tools that provide detailed tracking of the flock, increasing profitability, and protecting animals rationally. The Brazilian agricultural sector, due to weathering of the globalized world economy comes from increasingly, adapting the use of these automated tools to support decision making. Lameness is the most costly disease to confined milk cattle. Their causes cover climatic conditions, housing, feeding and the presence of more abrasive floors. Based on this information it is possible, using the correct algorithm to construct a model that allows the user to estimate the possibility of incidence of lameness in dairy cattle from historical data or other variables that cause the pathology. In this work the modeling was performed using the Universal Modelling Language (UML), of an expert system with a fuzzy inference engine for the preventive diagnosis of this condition that reduces the impact on production and cow comfort. From the modeling undertaken are available new foundation for future coding and building the expert system to mitigate the condition of the hull, reducing the impact of revenue losses related and expand the animal comfort.